Vocabulary Learning Strategies: An investigation of the EFL University Students - Oktaviani, Lulud; Wahyudin, Achmad Yudi (Indonesian Journal of Educational Studies, 2022)
Abstract. The mastery of lexical information is a constant struggle when studying English. It is not considered that having a large lexical knowledge or vocabulary is one of the conditions for being able to communicate smoothly in the language. Each student may have a different method for increasing their vocabulary. As a result, the purpose of this study is to learn about the tactics utilized by EFL students at one of Bandar Lampung's private universities. The study will also illustrate the frequency with which each method is employed by EFL students. The data for this study was collected via a distributed questionnaire and presented using a quantitative technique. This study enlisted the participation of 30 students from a private university in Bandar Lampung. The metacognitive method was shown to be the most frequently used strategy in acquiring English vocabulary, whereas the memory strategy was found to be the least frequently employed. Students typically prefer to watch English TV episodes or movies and observe their blunders as a technique to learn a new English language in specific actions. As shown in the findings of this study, certain tactics are less popular among students and should be offered since they will help students find the best way to acquire new vocabulary and eventually help them become independent learners.